God's relation to time : a thesis presented in fulfilment of the requirements for the degree of Master of Arts in Philosophy at Massey University, Tiritea [i.e. Turitea] Palmerston North, New Zealand - Shearman, Hayden Lloyd (Massey University, 2011)
Abstract not available
Keywords: Time; God; Philosophy; Theology; Relativism; Eternality; Change